Consumer Attributes in Buying Processed Fish in Kuala Bubon Village - Rahma Sawita; Yoga Nugroho (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
Kuala Bubon Village is one of the villages in the Samatiga sub-district where many of the residents work as fishermen and fish processors. In 2018 the number of industries and production of fish processing in Kuala Bubon Village there are 10 industries with a production output of 110,870 Kg.In addition to the salted fish processing area, there is also a processed fish stall. Consumers are the key in the buying and selling process. Processed fish traders in Kuala Bubon village do not yet know the importance of identifying what is the basis for consumers to buy processed fish, for that it is necessary to do research on consumer attributes so that they can know what to do for business sustainability. Collecting data using incidental sampling technique by way of interviews distributing questionnaires directly and through online. The method used in this study is a Likert scale with percentage analysis. From the research results obtained several attributes that become the basis of consumers in buying processed fish, namely service with a percentage value of 98.6%,then followed by convenience of place 94.2%, price 93.6%, hygienic place of sale 91.4%, distance and location of kiosks89.8%, the taste of processed fish 89.6%, the variety of types of fish sold 87.2%, recommendations from friends and neighbors 75.4%, and processed fish packaging 74.2%. with the results of this study, it is hope that it can become a reference for processed fish traders in managing their sales strategies and can improve business sustainability in terms of better production and marketing of processed fish. In addition, it is also hoped that it can be developed into research leads to strategies in making sustainable businesses in the fisheries sector.